2000
DOI: 10.1021/om000664h
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Terminal and Internal Acetylenes into the Zr−μ-Methylene Bond of the Dinuclear Cationic Zirconium Complex [{Zr(η5-C5H5)}2(μ-CH2)(μ-Cl)(μ-η5-C5H45-C5H4)][BMe(C6F5)3]. Synthetic Aspects, NMR Spectroscopic Study, and Dynamic Behavior in Solution

Abstract: The dinuclear cationic zirconium species [{Zr(η 5 -C 5 H 5 )} 2 (µ-CH 2 )(µ-Cl)(µ-η 5 -C 5 H 4 -η 5 -C 5 H 4 )]-[BMe(C 6 F 5 ) 3 ] (1) reacts in dichloromethane at -78 °C with terminal alkynes, via insertion into the Zr-µ-methylene bond, to give various dinuclear cationic derivatives. Reaction of 1 with Me 3 SiCtCH gives the hydrido complex [{Zr(η 5 -C[BMe(C 6 F 5 ) 3 ] (4). Compounds 3 and 4 show dynamic behavior in solution involving an interchange between two enantiomeric structures through a suprafacial mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…The behavior described here for compound 1c parallels that observed for the related dinuclear titanium compound [(TiBz 2 ) 2 (μ-{η 5 -C 5 H 4 SiMe 2 O} 2 )], for which the benzyl-bridged intermediate was unstable in aromatic solvents, decomposing to give unidentified paramagnetic species . The substitution of the benzyl by a halide bridge occurring in halogenated solvents is clearly favored by the π-donating ability of this substituent, which increases the electron density, reducing their positive charge. Cationic dinuclear group 4 complexes with halide bridges have also been formed by rearrangement of mononuclear cationic derivatives in halogenated solvents. ,, …”
Section: Resultssupporting
confidence: 71%
“…The behavior described here for compound 1c parallels that observed for the related dinuclear titanium compound [(TiBz 2 ) 2 (μ-{η 5 -C 5 H 4 SiMe 2 O} 2 )], for which the benzyl-bridged intermediate was unstable in aromatic solvents, decomposing to give unidentified paramagnetic species . The substitution of the benzyl by a halide bridge occurring in halogenated solvents is clearly favored by the π-donating ability of this substituent, which increases the electron density, reducing their positive charge. Cationic dinuclear group 4 complexes with halide bridges have also been formed by rearrangement of mononuclear cationic derivatives in halogenated solvents. ,, …”
Section: Resultssupporting
confidence: 71%
“…Intermediate A evolves via β-H elimination from the 1,3-μ 2 -propylene group to the more stable structure B ( rac isomer, Δ E = −16.1 kcal/mol) with a μ 2 -H bridge, methyl displacement toward to the Ti2 center, and a new allylic fragment at Ti1 . A similar Ti 2 complex, reminiscent of intermediate B , was observed experimentally by Cuenca et al . DFT yields similar results for meso- 5 ; however, intermediates A and B are far less stable than rac- 5 (Δ E = −1.7 kcal/mol and −2.5 kcal/mol for A and B , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…[25] It should be noted that the 1 H NMR spectrum of 1 displays two singlets for the Cp ligands and eight well-resolved multiplets (see the Experimental Section) for the fulvalene ligand (resulting in two ABCD spin systems). [19,26] We did not observe a Ga À H IR stretch in the expected region (1800-2100 cm À ). [27][28][29][30] In an effort to better elucidate the nature of the hydride, we performed density functional theory (DFT) computations on 1 a, in which the meta terphenyl ligand of 1 has been replaced with a 2,6-dimethylphenyl ligand.…”
mentioning
confidence: 48%
“…[11] The Ga ( . [19] Other 1 H NMR signals for bridging zirconium hydrides range from d = À5.32 to 0.95 ppm, [20][21][22][23] whereas terminal zirconium hydride 1 H NMR signals may range from d = 3.03 to 7.25 ppm. [20][21][22][23][24] The computed 1 H NMR spectrum of a model of 1, [(C 10 H 8 )(CpZr) 2 (m-H)(m-Cl)(mGaR)] (1 a; R = 2,6-Me 2 C 6 H 3 ), at the GIAO-PW91PW91/ LANL2DZ/-/PW91/LANL2DZ level showed that the computed hydride d value of À5.00 ppm is comparable to the experimental value observed for 1.…”
mentioning
confidence: 99%